Effect of planting geometry for single eye budded settling on growth, yield andquality of sugarcane under south Gujarat condition - Virdia, Hitesh; Patel, Vinjal; Patel, Jinal (Journal of Sugarcane Research, 2024)
A ﬁeld experiment was conducted for three years (2019-20, 2020-21 and 2021-22) at Main Sugarcane Research Station, Navsari Agricultural University (NAU), Navsari, Gujarat to study the effect of planting geometry for single eye budded settling on growth, yield and quality of sugarcane under South Gujarat condition. Five inter row spacing treatments comprising of planting single eye bud settling at 90 cm row spacing (R1), 105 cm (R2), 120 cm (R3), 60-120-60 cm pair row spacing (R4) and 90-120-90 cm pair row spacing (R5) and three intra row spacing viz., 30 cm (I1), 45 cm (I2) and 60 cm (I3) were evaluated in split plot design with three replications. In inter row spacing, planting single eye bud settling at 60-120-60 cm pair row spacing found signiﬁcantly superior for plant height (214 cm), number of tillers per plant (5.43), number of millable canes (95548), cane yield (199 t/ha) and CCS yield (14.02 t/ha). In intra row spacing, planting of single eye bud settling at 30 cm gave signiﬁcantly more plant height at 180 DAP (207 cm), number of millable canes (91243) and cane yield (113 t/ha) than rest of treatments. While number of tillers per plant (7.32) was highest under treatment I3 (planting of single eye bud settling at 60 cm). In case of economy, treatment R3 (120 cm inter row spacing) obtained higher net income (Rs. 252989/ha) and B:C ratio (2.56) followed by treatment R4(60-120-60 cm pair row spacing) with net income (Rs. 252892/ha) and B:C ratio (2.38). Among intra row spacing treatments, treatment I2 (45 cm recorded higher net return (Rs. 235008/ha). In case of B:C ratio, I3 (60 cm) recorded highest B:C ratio (2.47) followed by treatments I2(2.39). On the basis of pooled results, it is concluded from the study that higher yield and net returns of sugarcane crop can be achieved with planting single eye bud settling either at 120 cm row spacing or 60-120-60 cm pair row spacing; intra row spacing should be kept 45 cm under south Gujarat condition.